Riverman : [large type] an American odyssey - McGrath, Ben (Random House Large Print, 2022)
"The riveting story of Dick Conant, an American folk hero who, over the course of more than twenty years, solo canoed thousands of miles of American rivers--and then in 2014 disappeared off the coast of North Carolina"--